2016
DOI: 10.3389/fmicb.2016.01532
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-Activated Protein Kinase Kinase VdPbs2 of Verticillium dahliae Regulates Microsclerotia Formation, Stress Response, and Plant Infection

Abstract: Verticillium dahliae, a ubiquitous phytopathogenic fungus, forms resting structures, known as microsclerotia that play crucial roles in Verticillium wilt diseases. VdHog1, a mitogen-activated protein kinase (MAPK), controls microsclerotia formation, virulence, and stress response in V. dahliae. In this study, we present detailed evidence that the conserved upstream component of VdHog1, VdPbs2, is a key regulator of microsclerotia formation, oxidative stress and fungicide response and plant virulence in V. dahl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 78 publications
(107 reference statements)
1
46
0
Order By: Relevance
“…dahliae (Figs B, , and , Fig. S8), and the role of the MAPK pathways in melanin biosynthesis is well characterized (Tzima et al ., ; Tian et al ., ; Tian et al ., ; Wang et al ., ; Yu et al ., ; Zheng et al ., ). Although VdSho1 did not show significant growth changes in response to nystatin, melanin accumulation, however, affected the membrane permeability mediated by nystatin treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…dahliae (Figs B, , and , Fig. S8), and the role of the MAPK pathways in melanin biosynthesis is well characterized (Tzima et al ., ; Tian et al ., ; Tian et al ., ; Wang et al ., ; Yu et al ., ; Zheng et al ., ). Although VdSho1 did not show significant growth changes in response to nystatin, melanin accumulation, however, affected the membrane permeability mediated by nystatin treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, gene deletion studies of various MAPK cascade components suggest a strong correlation between melanin biosynthesis and virulence in V . dahliae (Tzima et al ., ; Tian et al ., ; Tian et al ., ; Wang et al ., ; Yu et al ., ; Zheng et al ., ). Thus, the degree of influence of melanin may be contingent on the strain, and the host type challenged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also confirmed that VDH1, encoding a class II hydrophobin, is involved in the formation of microsclerotia (Klimes et al 2008;Klimes and Dobinson 2006). In addition, many genes have been characterized that are involved in signal transduction pathways and regulation of microsclerotia formation of V. dahliae, such as VMK1, encoding a mitogen-activated protein kinase (Rauyaree et al 2005), VdGARP1, encoding a glutamic acid-rich protein , the G protein β subunit (named as VGB) (Tzima et al 2012), Vta2, encoding a nuclear zinc finger protein, (Tran et al 2014), the MADS-box transcription factor VdMcm1 , the mitogen-activated protein kinase (MAPK) Hog1 , and the MAPK Msb and Pbs2 Tian et al 2016). Unravelling the functional characterizations of these genes provides insight into the genetic control of microsclerotia formation in V. dahliae.…”
Section: Disease Cycle Of Verticillium Wilt Of Treesmentioning
confidence: 99%